Utilization of Assistive Technology in Special Needs Children's Learning (Inclusive Education) - Herry Widiyastono; Dewi Sri Rejeki; Mahardika Supratiwi; Gunarhadi Gunarhadi; Joko Yuwono; Hermawan Hermawan (Journal of Disability, 2023)
This study aims to: a) assess teachers' understanding of assistive technology, and b) explore the benefits of assistive technology in the education of children with special needs in inclusive schools. The research was conducted in an inclusive elementary school located in Boyolali, involving both teachers and children with special needs in inclusive education. Data collection methods included closed and open-ended questionnaires and interviews with teachers in inclusive schools. Data analysis employed both quantitative and qualitative descriptive techniques. The research findings indicate that a) 33% of teachers do not yet comprehend the use of assistive technology in education, and b) 48% of teachers require assistance in utilizing assistive technology for the education of children with special needs in inclusive schools. It is expected that the results of this research will serve as a reference for all stakeholders to pay more attention to the importance of utilizing assistive technology in the education of children with special needs in inclusive schools.